Toitū Te Iwi - A Journey in the Evolution of Cultural Identity - O’Regan, Hana (Te Kaharoa, 2009)
This article focuses on themes associated with identity and identity development pertaining to indigenous minorities, Maori, and more specifically the author’s own tribal people, the Ngai Tahu. The subject is examined through a personal odyssey and offers insights on aspects of cultural identity in a contemporary setting.